KNOWLEDGE ON PREVENTION OF SEXUAL TRANSMISSION INFECTIONS IN INMIGRANT ADOLESCENTS IN SOLEDAD-ATLANTICO 2018-2019 - GUERRA RAMIREZ, MERILYN (2020)
In recent years, interest in the study of adolescence and the debut of sexual and couple relationships that frequently present sexual and reproductive health discomforts, which is manifested in the increase in sexually transmitted infections and pregnancies, have increased not wanted. At the same time, the problem caused by the phenomenon of migration means that in most cases this population has diﬃcult access to a health institution, which does not allow for early diagnosis and timely treatment. This work aims to assess the knowledge about prevention of sexually transmitted infections in immigrant adolescents living in Soledad-Atlántico 2018-2019. A quantitative methodology with a quantitative descriptive approach was used, the population under study were 234 immigrant adolescents in the range of 10-19 years and accessing health services at a public institution in Soledad-Atlántico. It was possible to deduce through the survey the knowledge that adolescents have about sexually transmitted infections, the result indicates that the level of knowledge is medium, and they aﬃrm that it is of great importance that young people acquire knowledge about STIs. Education to the vulnerable population is urgent as a method of prevention and contribution to health with emphasis on strengthening the Integral Education of Sexuality through the promotion of healthy sexual behaviors.